Career paths and postretirement adjustment among Spanish elite-athletes - Lopez de Subijana, C.; Barriopedro, M.; Muniesa, C.; Gomez-Ruano, M. A. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
The study presented by Pallarés, Azocar, Torregrosa, Selva, and Ramis (2011) proposed three types of sport career paths: i) linear: where the athlete gives exclusive dedication to sport; ii) convergent: in which the athlete prioritises the sport career but he/she maintains another activity (i.e., study or work); and iii) parallel: where the athlete places equal importance on the sport career and the alternative activity. Particularly, the available research has been focused on how athletes who follow a "dual career" (DC) are less likely to suffer difficulties regarding their social and labor market integration after their sport career (Tekav, Wylleman, & Cecir Erpic, 2015). Thus, the aims of the present study were to analyze whether the type of career path chosen is related to: i) their academic level, ii) the labor market integration; and iii) the difficulties experienced after the retirement. Methods: An adaptation of the Athlete`s Retirement Questionnaire (Alfermann, Stambulova & Zemaityte, 2004) was fulfilled by 178 retired athletes (n= 109 male and n= 69 female; 39±7 years). Results: Most of the athletes combined the studies and sport while they were at the mastery stage of their sport career, in the convergent (40.1%) or in the parallel (30.5%) way. Only 15.3% of the athletes were focused solely on the sport. The career path was not independent of the gender. More female than male combined studies and sport in a parallel way (39.1% vs. 25.0%) while more male than female followed a DC combined with their work (18.5% vs. 7.2%) or were focused solely on the sport (20.4% vs. 7.2%). Significant differences were found regarding the academic level reached according to the model chosen for male but not for female. The male athletes who followed a career path combining the studies and the sport in a convergent or in a parallel way reached a higher academic level than those who were focused solely on the sport and those who combined working and the sport. In addition, the results showed that 87.0% of the male and 89.9% of the female athletes were employed and no differences were found in the income level of the athletes according to the career path. Neither gender nor career path were related to the difficulties experienced after the retirement. The most important difficulties perceived by the athletes were the financial (2.35±1.43) and social-relationships problems (2.18±1.40). Conclusions: The career path followed during the mastery stage does not make a difference in the quality of life after the sport career. The results point out that combining the sports with the studies ensures the achievement of higher education studies for male athletes. However, no income level differences were found after the sport retirement.